(untitled) (PANGEEA, 2025)
Geographical toponyms can provide important information about the history of geological, geomorphological and social territories or natural or social phenomena. On the basis of place names in Romania (Criş, Bihor, Zarand, Transilvania, Mureş, Ampoi, Dunăre, Bărăgan etc.), attempt to decipher the natural or social events of the past of this areas.